Urgency of Islamic Civil Law in Heritage Aspect - Tb Syaiful Hidayat (IHSA Institute, 2021)
This research was conducted in order to obtain information data about inheritance issues in Indonesia in the aspect of Islamic Civil Law, so as to provide a correct understanding to the public about the urgency of the state in resolving inheritance problems. Islamic Civil Law in Indonesia is formulated in the Compilation of Islamic Law which is expected to accommodate all debates on inheritance issues, so that it can provide legal force in a juridical format and serve as guidelines in Indonesian law. This research also uses the literature study method in order to obtain data related to the problems studied. Research is expected to be a reference for readers to what extent the urgency of inheritance in Islam in order to provide rights based on the principle of justice.